The Effect of Service Quality on Housing Security Management toward Consumer Satisfaction on Housing Lecturer of Hasanuddin University in Makassar - Sumarsih Sumarsih; Zainal Abidin (Research Synergy Foundation, 2019)
The purpose of this study is to: 1) analyze the effect of service quality which consisting of reliability, responsiveness, empathy, assurance, and physical appearance to customer satisfaction on the Housing Security Management Lecturer of Hasanuddin University Tamalanrea in Makassar; and 2) to know the dominant variable affecting the consumer satisfaction on the Housing Security Management Lecturer Hasanuddin University Tamalanrea in Makassar. The data used are primary and secondary data. The population of the study is 644 people as consumers who are living in Housing Lecturer Hasanuddin University Tamalanrea in Makassar. The methods of sampling in this study using Slovin formulation consisted of 247 respondents. The data collection, which is used is questionnaires and documentation. Methods of data analysis using descriptive statistical analysis, and multiple linear regression using SPSS Program. The results showed that simultaneously variable reliability, responsiveness, empathy, assurance, and physical appearance, have a positive and significant impact on the satisfaction of consumers in the Housing Security Management Lecturer Hasanuddin University Tamalanrea in Makassar. Furthermore, the partial variables reliability, empathy, and assurance have a positive and significant impact on customer satisfaction, while the variable responsiveness and physical appearance have no significant effect on customer satisfaction. Among three variables that significantly influence it, it turns out the variable reliability that can improve the Consumer Satisfaction on Security Management Housing Lecturer Hasanuddin University Tamalanrea in Makassar.